MOFs (METAL-ORGANIC FRAMEWORKS): UMA FASCINANTE CLASSE DE MATERIAIS INORGÂNICOS POROSOS - Frem, Regina C. G.; Arroyos, Guilherme; Flor, Jader B. Da Silva; Alves, Renata C.; Lucena, Guilherme N.; Silva, Caroline M. Da; Coura, Mariana F. (Sociedade Brasileira de Química, 2018)
Metal-Organic Frameworks (MOFs) are, according to IUPAC, coordination polymers with an open framework containing potential voids, which can be accessible after activation processes. These materials have aroused interest in the academic environment – and more recently in industry - because their properties such as high crystallinity, permanent microporosity, high surface areas, and the possibility of functionalization. This has enabled applications in different areas, such as gas adsorption, catalysis, drug delivery, photonics and others. Depending on the judicious choice of the metals and the organic linkers, MOFs with different topologies and functions can be created. Synthetic routes for the preparation of these materials will be discussed, highlighting those in consonance with the Green Inorganic Chemistry. Strategies for controlling the size and morphology of the crystals will also be presented, as well the most recent methodologies for the large-scale production. This review will also discuss the use of MOFs in the context of energy and environment, particularly referring to the adsorption and/or transformation of CO2, storage of H2 and CH4 as well potable water capture.
MOFs (METAL-ORGANIC FRAMEWORKS): A FASCINATING CLASS OF POROUS INORGANIC MATERIALS
Keywords: MOFs; porous materials; reticular chemistry; green inorganic synthesis; environment and energy